EVALUASI SISTEM INFORMASI PERSEDIAAN PADA PT SUMBER MANDIRI - Suryanto, Suryanto; Gondodiyoto, Sanyoto; Ristianto, Ristianto; Herny, Herny; Nathalia, Devi (CommIT (Communication and Information Technology) Journal, 2009)
Inventory is a resource that is stored for the production process or for the sale of a business process. The purpose of this paper is to study and analyze current procedures and business in the information system implemented in the company’s inventory, measure the effectiveness and efficiency of inventory control information system that is applied, knowing the strengths and weaknesses in the implementation of information systems inventory by the company, so it can provide recommendations and suggestions for improving the existing weaknesses. The method used in preparing this paper the writer is literature study, observation, interviewing relevant parties, check list, application testing, and documentation study. Observations collected will be analyzed, evaluated and compared with the theory of internal control. Based on the results of evaluation writers, inventory information system procedures performed PT Sumber Mandiri was good enough, although there are still some weaknesses. In this case the company should fix these weaknesses to improve operations and performance.Keywords: evaluation, information systems inventory, general control, application control